Financial markets meltdown: What can we learn from Minsky? - L. Randall Wray (Levy Economics Institute of Bard College, 2008)
In this new Public Policy Brief, Senior Scholar L. Randall Wray explains today's complex and fragile financial system, and how the seeds of crisis were sown by lax oversight, deregulation, and risky innovations such as securitization. He estimates that the combined losses throughout the entire financial sector could amount to several trillion dollars, and that the United States will feel the effects of the crisis for some time - perhaps a decade or more. Wray recommends enhanced oversight of financial institutions, much larger stimulus packages, and creation of a new institution in line with President Franklin D. Roosevelt's Home Owners' Loan Corporation.
Keywords: 330